Verejné obstarávanie v dopravnej infraštruktúre Slovenska v rokoch 2010-2015 - Tkáčová, Andrea; Danko, Jakub; Zitrický, Andrej (Univerzita Pardubice, 2016)
Ensuring quality transport infrastructure requires considerable financial resources from the state which can be optimized through public procurement. Research studies of domestic and foreign authors identified several variables that affect the resulting savings in public procurement. In our contribution we focused on creating models that examine the impact of the number of offers, subcontractor participation and type of procurement procedure for this savings. We analyzed 178 public procurement contracts in the field of transport infrastructure in Slovakia in the years 2010-2015. For detection of relationship between these chosen variables and saving in public procurement were used method as second order polynomial regression and Wilcoxon signed-rank test in the program R.
Public Procurement in Transport Infrastructure of Slovakia between 2010-2015
Keywords: Public procurement; Transport infrastructure; Public contract; Saving; Second order polynomial regression; H40; H54